2001
DOI: 10.1093/emboj/20.4.767
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that a protein-protein interaction 'hot spot' on heterotrimeric G protein betagamma subunits is used for recognition of a subclass of effectors

Abstract: To understand the requirements for binding to G protein betagamma subunits, phage-displayed random peptide libraries were screened using immobilized biotinylated betagamma as the target. Selected peptides were grouped into four different families based on their sequence characteristics. One group (group I) had a clear conserved motif that has significant homology to peptides derived from phospholipase C beta (PLC beta) and to a short motif in phosducin that binds to G protein beta subunits. The other groups ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(99 citation statements)
references
References 41 publications
3
96
0
Order By: Relevance
“…The current data with AGS8 in both the yeast and mammalian systems along with the recent reports regarding direct regulation of G␤␥ (27,28) and diversity of G␤␥ binding partners (29,30) suggest that G␤␥ may possess additional protein binding sites for signal processing (28,31). Such G␤␥ binding partners may serve as effectors for mammalian G␤␥, influence receptor coupling to G␣␤␥ or localize G␤␥ within a larger signaling complex, where it can regulate specific signaling pathways independent of the classical heterotrimeric G␣␤␥.…”
Section: Resultsmentioning
confidence: 69%
“…The current data with AGS8 in both the yeast and mammalian systems along with the recent reports regarding direct regulation of G␤␥ (27,28) and diversity of G␤␥ binding partners (29,30) suggest that G␤␥ may possess additional protein binding sites for signal processing (28,31). Such G␤␥ binding partners may serve as effectors for mammalian G␤␥, influence receptor coupling to G␣␤␥ or localize G␤␥ within a larger signaling complex, where it can regulate specific signaling pathways independent of the classical heterotrimeric G␣␤␥.…”
Section: Resultsmentioning
confidence: 69%
“…25 Physical basis of specific interactions on the protein surface has recently become the subject of intense experimental and theoretical studies. [29][30][31][32] The concept of protein interaction hot spots has been put forward. 29 It has been proposed that only a small set of hot spot residues may contribute to binding free energy and the presence of , and CA bound A-crystallin.…”
Section: Discussionmentioning
confidence: 99%
“…hot spots are general characteristics of protein-protein interfaces. 30,31 It has been suggested that conserved polar residues constitute hot spots but many interaction hot spots involve hydrophobic or large aromatic residues as well. 29,32 Such specific interactions may be responsible for the action of -crystallin against -and -crystallin, while the nonspecific interaction may be responsible for its chaperone-like activity against other substrates.…”
Section: Discussionmentioning
confidence: 99%
“…One is that a key interaction surface on Gβγ normally occluded by Gα subunits, mediates interactions with multiple effectors (Ford et al, 1998;Li et al, 1998). This region has been characterized as a "hot spot" that accommodates binding to structurally diverse effectors (Scott et al, 2001). "Hot Spots" are surfaces on proteins that by virtue of steric adaptability and the ability to form multiple types of chemical interactions are particularly well suited for mediating the energetics of diverse protein-protein interactions (Clackson and Wells, 1995;DeLano, 2002).…”
Section: Effector Recognition By G Protein βγ Subunits -"Hotspots" Anmentioning
confidence: 99%
“…Peptides that bind to the G protein "hot spot" were recently identified in a random peptide phage display screen (Scott et al, 2001). One of these peptides SIRK, has unique properties in that it binds directly at the α-subunit switch II binding site on Gβγ and actively promotes subunit dissociation (Davis et al, 2005;Scott et al, 2001). In addition, SIRK blocked activation of PLCβ and PI3K in vitro by Gβγ, yet stimulated Gβγ -regulated ERK activation in intact cells.…”
Section: Activation Of G Protein βγ Subunit Signaling By G Protein βγmentioning
confidence: 99%